2021
DOI: 10.3390/membranes11060433
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanoparticle Filler-Based Mixed-Matrix PES/CA Nanofiltration Membranes for Enhanced Desalination

Abstract: Mixed-matrix nanocomposite (PES/CA/PVP) membranes were fabricated for water desalination by incorporating varying amount of titanium dioxide nanoparticles (TiO2 NPs) ranging from 0 and 2 wt. %. Efficient dispersion of nanoparticles within polymeric membranes was achieved using the chemical precipitation method for uniform surface generation, and an asymmetric morphology was achieved via phase inversion method. Finally, membranes were characterized by Fourier Transform Infrared (FTIR) spectroscopy, Thermo Gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 70 publications
4
13
0
Order By: Relevance
“…The findings of employing GO as a nanofiller material for nanofiltration membranes are consistent with the reported data by Hao et al [25] and Amin et al [61]. TiO 2 nanomaterial, which is utilized in nanofiltration, also improves the water flux [66][67][68].…”
Section: Efficiency Of Oil Removalsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of employing GO as a nanofiller material for nanofiltration membranes are consistent with the reported data by Hao et al [25] and Amin et al [61]. TiO 2 nanomaterial, which is utilized in nanofiltration, also improves the water flux [66][67][68].…”
Section: Efficiency Of Oil Removalsupporting
confidence: 90%
“…These findings are in line with those of Mehwish et al, who discovered that TiO2 NP can improve the chemical stability of PES membranes [66]. Yeh et al have shown the remarkable stability of GO membranes in water [67]. The successful use of 1 M NaOH as a cleaning agent with a high FRR demonstrates membrane resilience to cleaning.…”
Section: Alkaline Resistance Of Membranessupporting
confidence: 89%
“…Several investigators have studied the preparation of different chalcogenides. The electro-luminescence, as well as numerous diffractive properties of Nano-composites of chalcogenides/polymer, has lately been explored 1 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnologies are making their way into all features of our survival; these technologies are being progressively used in pharmacological and medicinal applications, makeups and individual products, energy storing and effectiveness, water treatments and air purification, environmental remediation, chemical as well as biological antennas, military defense and explosives [1], and in numerous consumer products and material. For instance, in the area of food, nanomaterials can be used to provide new tastes and flavors; functional food; hygienic food dispensation and packing; intelligent, frivolous, and strong packing; extended shelf life; and concentrated agrochemicals, colors, flavors, and preservers [2].…”
Section: Introductionmentioning
confidence: 99%